ASSOCIATION OF GOVERNMENT POLICY AND MOTHER’S PERCEPTION TO EXCLUSIVE BREASTFEEDING PRACTICE - Mufdlilah Mufdlilah; Muhammad Akhyar; Endang Sutisna; Ahmad Arman Subijanto (Belitung Nursing Journal, 2016)
Background: Although the Indonesian government has campaigned exclusive breastfeeding during the past decade through maternal and child program of Ministry of Health, however, its coverage in Yogyakarta province remains low. Objective: This study aims to analyze factors related to exclusive breastfeeding program, especially indicators that can explain government’s regulation and mothers’ perception to exclusive breastfeeding practice. Methods: It was a cross-sectional study involved 185 mothers who have 6-12 months infants with parity 1-3. The correspondents live in Sleman district and had normal delivery in hospital, health center or midwifery private practitioner. The association between the exogenous (government policy and mothers’ perception) and the endogenous variables (mothers’ participation to exclusive breastfeeding practice) was determined using Lisrel version 8.80. Results: Although the government policy contributed to the success of implementing breastfeeding program (33%), providing breastfeeding rooms (28%), and declaring the related government regulation (17%); however, its contribution was recorded at only 2% to human resources. Knowledge significantly encouraged mothers to breastfeed whilst infrastructure was assessed as a strong determinant of mothers’ willingness to participate in the program at the contribution of 50%. Conclusion: Although there was only a weak association between government regulation to mothers’ perception and between mothers’ perception towards exclusive breastfeeding practice, the study highlights the importance of providing adequate information to improve mothers’ knowledge on exclusive breastfeeding. By knowledge improvement, mothers will have better perception, which in turn will improve their self-efficacy and practices in exclusive breastfeeding.